Technical and Social Evaluation of Arsenic Mitigation in Rural Bangladesh - Shafiquzzaman, Md; Azam, Md Shafiul; Mishima, Iori; Nakajima, Jun (Journal of Health, Population and Nutrition, 2009)
Technical and social performances of an arsenic-removal technology-the sono arsenic filter-in rural areas of Bangladesh were investigated. Results of arsenic field-test showed that filtered water met the Bangladesh standard (<50 ?g/L) after two years of continuous use. A questionnaire was administrated among 198 sono arsenic filter-user and 230 non-user families. Seventy-two percent of filters (n=198) were working at the time of the survey. Another 28% of the filters were abandoned due to breakage. The abandonment percentage (28%) was lower than other mitigation options currently implemented in Bangladesh. Households were reluctant to repair the broken filters on their own. High cost, problems with maintenance of filters, weak sludge-disposal guidance, and slow flow rate were the other demerits of the filter. These results indicate that the implementation approaches of the sono arsenic filter suffered from lack of ownership and long-term sustainability. Continuous use of arsenic-contaminated tubewells by the non-user households demonstrated the lack of alternative water supply in the survey area. Willingness of households to pay (about 30%) and preference of household filter (50%) suggest the need to develop a low-cost household arsenic filter. Development of community-based organization would be also necessary to implement a long-term, sustainable plan for household-based technology. J Health Popul Nutr 2009 Oct; 27(5):674-683